Performance analysis of Cu-MWCNT bundled HCTSVs using ternary logic - Katepogu Rajkumar; G． Umamaheswara Reddy (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
This paper presents an investigation of crosstalk issues for coupled heterogeneous coaxial through silicon vias (HCTSVs) in ternary logic. Crosstalk issues are investigated for coupled HCTSVs using Cu-MWCNT as a conductive filler and polymer liners such as polyimide, polypropylene carbonate (PPC), and benzocyclobutene (BCB) as insulating materials. The electrical equivalent circuit model is utilized to investigate the crosstalk induced by the ternary inverter in coupled HCTSVs. The effects of crosstalk such as functional and dynamic crosstalk for proposed HCTSVs are compared with Multi-walled CNT (MWCNT) TSVs using Hewlett simulation program with integrated circuit emphasis (HSPICE) simulations. Other performance parameters are also investigated, including power dissipation, power delay product (PDP), and energy delay product (EDP). The proposed model's crosstalk effects are also investigated for various TSV heights. The BCB-based coupled Cu-MWCNT HCTSVs provide a significant improvement in crosstalk at reduced TSV height. The proposed HCTSVs also improved overall performance by 32.12% when compared to the MWCNT based TSVs. As a result, Cu-MWCNT based HCTSVs with BCB liner are better than conventional TSVs for ternary logic integrated circuits (ICs).